Haemolytic Effects of Hypo-osmotic Salt Solutions on Human Erythrocytes - Nepal, O; Rao, J P (Kathmandu University Medical Journal, 2012)
Background While it is well known that hypotonic solutions of sodium chloride induce hemolysis, the effects of other salt solutions on human erythrocytes have not been well documented. Objective The study is to compare the effects of other salt solutions on human red cells. Methods Iso-osmotic and hypo-osmotic solutions of various salts were prepared after taking into account their molecular weight and osmotic pressure. Five healthy volunteers between the age of 22-30 years were randomly selected and ten blood samples were collected from them. The study was conducted from January 2009 to February 2009. Blood was collected from subjects by venepuncture into heparinised tubes. 20 ?l of blood was pipetted into 1 ml of each solution and incubated for one hour at 37ºC in a water bath. The solutions were centrifuged and the colour of the supernatant was read in a spectrophotometer. Supernatant from blood added to distilled water was considered 100% hemolysed. Results Iso-osmotic salt solutions were free of hemolysis. Among chloride salts, sodium chloride showed the least hemolysis and potassium chloride and nickel chloride resulted into greater hemolysis. Among potassium salts, potassium bromate caused highest amount of hemolysis whereas potassium sulphate showed the least. Conclusion The significant differences in hemolytic pattern in hypo-osmotic salts solutions suggest that the hypo-osmotic stress causes morphological changes in red cells that alter their permeability to various ions leading to hemolysis. This probably occurs through opening of volume sensitive channels. DOI: http://dx.doi.org/10.3126/kumj.v9i2.6285Kathmandu Univ Med J 2011;9(2):35-9